(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2021)
Within the political-religious conflict “la Cristiada”, which arose in 1926 until 1929, mainly in the north-central area of Mexico, activities were carried out by women’s brigades in support of and assistance to the armed movement. The purpose of this text is to analyze the dynamics of women in Mexican society in the 1920s, making visible their activities as mothers, nurses, brigadistas and guerrillas, active participants in the conflict. In this way, it seeks to vindicate the image of these groups of women who acted as a key piece in the development of the event, through new approaches in its study and historiographic interpretation. The topic will be developed from a mixed methodology that addresses the methods of social history, in relation to approaches and some techniques from social anthropology, in collaboration with each other to enable a broader analysis of the problem. In this sense, comparative analogies will be established between the different activities of the groups of women cristeras, with the purpose of displacing the wrong image that has been built around their participation and relevance the development of the armed movement. Obtaining as a result that the motivations that characterized the cristeros groups were cemented by them from the bosom of the home, since, through the role of mothers as the main natural activity, were those who sustained the social commitment to perpetuate in children and spouses a religious identity.